2010
DOI: 10.1007/s11136-010-9719-0
|View full text |Cite
|
Sign up to set email alerts
|

Solitary pulmonary nodules: consequences for patient quality of life

Abstract: Six months after receiving a diagnosis of SPNs, whether malignant, patients have worse HRQoL compared to the French general population. It indicates areas where physicians can help patients coping with their disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 36 publications
2
9
1
Order By: Relevance
“…3,710,24,25 Yet, our results differ somewhat from the literature on the impact of screen-detected pulmonary nodules. 15,2628 Some lung cancer screening trials do suggest that patients experience mild short-term distress, 15 anxiety, 29 or impairments in quality of life 30 after nodule detection.…”
Section: Discussioncontrasting
confidence: 99%
“…3,710,24,25 Yet, our results differ somewhat from the literature on the impact of screen-detected pulmonary nodules. 15,2628 Some lung cancer screening trials do suggest that patients experience mild short-term distress, 15 anxiety, 29 or impairments in quality of life 30 after nodule detection.…”
Section: Discussioncontrasting
confidence: 99%
“…Lemonnier et al compared health-related quality of life measures in 171 patients with pulmonary nodules 1–3 cm in diameter with those of the general population with a similar age 320. They found that patients with pulmonary nodules had worse self-reported health status (as measured by a reduction in score on the Short Form 36 Health Survey of between 11 and 30 points), which was most marked for older people and those who were smokers.…”
Section: Information and Supportmentioning
confidence: 99%
“…A prospective multi-center study was conducted in northeastern France (Alsace, Lorraine, Franche-Comté, Bourgogne, and Champagne-Ardenne) as part of research reported elsewhere [22-24]. The study involved 18 health-administrative districts covering 8.22 million people.…”
Section: Methodsmentioning
confidence: 99%